Genotype profiles for the Costa Rican population at 7 PCR-based loci - Morera, Bernal (Universidad de Costa Rica, 2004)
Complete electronic DNA profiles of 2006 randomly selected Costa Ricans, typed for 7 PCR-based loci, are presented. Such data may prove valuable for anthropological and forensic studies of the Costa Rican population.